Analysis Of Nahwu Errors In Hamzah Washl And Hamzah Qath’i Class 5 KMI At Gontor For Girls/ تحليل الأخطاء النحوية في همزة الوصل وهمزة القطع لدى الطالبات الصف الرابع بمعهد كونتور للبنات - Zaid, Abdul Hafidz; Putri, Syifa Firdausi; Anggraini, Reyka Mei (Ijaz Arabi Journal of Arabic Learning, 2025)
Writing is a critical communication skill used to express ideas and is highly valued in language education. One of the language elements that must be mastered for writing is hamzah washl and hamzah qath'i. This research is based on the phenomenon of student’s Arabic writing errors in the Gontor for Girls 1st campus. They are able to write Insya’ in Arabic but find it challenging to apply hamzah washl and hamzah qath'i in their writing. This research aims to identify and analyze writing errors in hamzah washl and hamzah qath'i class 5 KMI in Gontor for Girls 2024-2025. The method used in this research is qualitative research with a descriptive approach. The data collection technique used is through documentation of Insya’ Usbu’i writing. The results of this research showed that errors were found in using hamzah washl and hamzah qath'i. The writing errors in hamzah washl are in: fi’il maadhi tsulatsiy, mashdar khumasiy, isim asyroh, and at-ta’rif. The writing errors in hamzah qath’i are in all content sentences except isim asyroh, fi’il mudhari’ starting with hamzah, fi’il madhi tsulatsiy, and fi’il madhi ruba’iy. Teachers should pay more attention to the hamzah washl and hamzah qath'i material and provide students with more practice with it to enhance the quality of Arabic language education.